Uridine affects amino acid metabolism in sow-piglets model and increases viability of pTr2 cells - Wang, Hong-ling; Liu, Yilin; Zhou, Tiantian; Gao, Lumin; Li, Jianxi; Wu, Xin; Yin, Yu-long (Frontiers in Nutrition, 2022)
BACKGROUND: As an important nucleoside precursor in salvage synthesis pathway of uridine monophosphate (UMP), uridine (UR) is the most abundant nucleotide in sow milk. This study tested the effects of maternal UR supplementation during second trimester of pregnancy on reproductive performance and amino acid metabolism of Sows. RESULTS: Results showed that compared to CON group, the average number of stillborn piglets per litter was significantly reduced (P < 0.05) with higher average piglet weight at birth in UR group (P = 0.083). Besides, dietary UR supplementation significantly increased TP in sow serum, BUN content in cord serum, and TP and ALB in newborn piglet serum (P < 0.05); but decreased AST level in sow serum and BUN level in piglet serum (P < 0.05). Importantly, free amino acids profile in sow serum newborn piglet serum and colostrum was changed by maternal UR supplementation during second trimester of pregnancy, as well as the expression of amino acids transporter (P<0.05). In addition, from 100 to 2000 μM UR can increased cell viability of pTr2 cells. The UR exhibited higher distribution of G1/M phase of cell cycle at 400 μM compared with 0 μM, and reduced S-phases of cell cycle compared with 0 and 100μM (P<0.05). CONCLUSIONS: Supplementation of uridine during the second trimester of pregnancy can improve reproductive performance, regulate amino acid metabolism of sows and their offspring, and increase the viability of viability of pTr2 cells.